Let α 1 , … , α d , β 1 , … , β e ∈ C be such that the polynomials
f 1 ( x ) = ∏ i = 1 d ( x − α i ) and
f 2 ( x ) = ∏ i = 1 e ( x − β i ) have integer coefficients.
Suppose that there exist polynomials g 1 , g 2 ∈ Z [ x ] such that f 1 g 1 + f 2 g 2 = 1
Then the value of
∣ ∣ ∣ ∏ i = 1 d ∏ j = 1 e ( α i − β j ) ∣ ∣ ∣ is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
So this uses most of the Galois theory part and ring theory?
Problem Loading...
Note Loading...
Set Loading...
Given p ( x ) ∈ Z [ x ] , the polynomial
q ( x 1 , … , x m ) = ∏ i = 1 m p ( x i ) , is a symmetric polynomial in Z [ x 1 , … , x m ] . By the fundamental theorem of symmetric polynomials q ( x 1 , … , x m ) = r ( s 1 , … , s m ) where the s i are the elementary symmetric polynomials , and r ∈ Z [ x 1 , … , x m ] (in fact the coefficients of r are uniquely given by the coefficients of q ). Now if f 1 ( x ) = x m − c 1 x m − 1 + … + ( − 1 ) m c m . Then q ( a 1 , … , a m ) = r ( c 1 , … , c m ) (by Viète's formulas). This means that ∏ i = 1 m p ( a i ) ∈ Z for any p ( x ) ∈ Z [ x ] . ( ∗ ) Finally evaluating f 1 g 1 + f 2 g 2 = 1 in a i for i = 1 , … , m it follows that f 2 ( a i ) g 2 ( a i ) = 1 and then
∏ i = 1 m f 2 ( a i ) ∏ i = 1 m g 2 ( a i ) = 1
by ( ∗ ) both ∏ i = 1 m f 2 ( a i ) and ∏ i = 1 m g 2 ( a i ) are integers. So ∏ i = 1 m f 2 ( a i ) is a unity of Z , then it is 1 or − 1 , equivalently
∣ ∏ i = 1 m f 2 ( a i ) ∣ = 1 but this is just ∣ ∏ i = 1 m ∏ j = 1 n ( a i − b j ) ∣ = 1